Morphological Features in Sunflower as Influenced by Varying Nutritional Area - Haji A. Bukhsh, M. Ahmad Alias; Kaleem, Shuaib; Ishaque, M.; Iqbal, Javaid; Randhawa, Mahmood A.; Rasheed, M.; Khan, Hammad A. (Pakistan Journal of Nutrition, 2011)
Agronomic traits ultimately contribute to final achene yield. Any improvement in agronomic traits means increase in achene yield. For this purpose, a field trial was conducted at experimental area of Agronomy Department, PMAS Arid Agriculture University, Rawalpindi during two consecutive years 2008 and 2009 to evaluate the performance of two sunflower hybrids i.e S-278 and Hysun-33 under different levels of nutritional area i.e, 60 x 20, 60 x 30, 60 x 40, 60 x 50, 60 x 60 (with 1 plant/hill) and 60 x 60 cm-2 (with 2 plants hill). The experiment was laid out in randomized complete block design with three replications in split plot arrangement keeping nutritional areas levels in main plot and sunflower hybrids in sub plot effects. It was observed that among sunflower hybrids, S-278 produced significantly taller plants, heavier 1000-achene weight, higher achene and stalk yield, but lesser harvest index than these in Hysun-33. Both hybrids were, however, similar for head diameter and number of achene/head. Sunflower hybrid Hysun-33 planted at nutritional area of 60 x 20 cm2 produced the highest achene yield (2.89 t/ha), which was also statistically at par with other treatments; whereas sunflower hybrid S-278 planted at nutritional area of 60 x 40 cm2 produced the lowest achene yield (2.45 t/ha). Likewise, sunflower hybrid Hysun-33 planted at nutritional area of 60 x 40 cm2 computed the highest harvest index (37.75%), which was also statistically at par with other treatments; whereas sunflower hybrid S-278 planted at nutritional area of 60 x 20 cm2 computed the lowest harvest index (31.00%). It is therefore suggested that sunflower hybrid S-278 should be cultivated at level of nutritional area of 60 x 20 cm2 to get maximum achene and stalk yield.